A car travels first half distance between two places with a speed of 40 kilometre per hour and rest of half distance with a speed of 60 km per hour. The average speed of car is:

Let the total distance covered be"s" km.

Total time taken,

=(s/2)/30+(s/2)/60

=3s/120

Average speed,

=s/(3s/120)

=s(120/3s)

=40 km/hr

.
In following questions, one term in number series is incorrect.

Find out the incorrect number 15, 16, 22, 29, 45, 70

Find out the incorrect number 15, 16, 22, 29, 45, 70

The pettern is + 1, + 4, + 9, + 16, + 25,.... i.e. + 1

So, 22 is wrong and must be replaced by (16 + 4) i.e. 20..

In following questions, a sequence of groups of alphabets and numbers is provided with one term missing , Choose the missing term from options.

QPO, SRQ, UTS, WVU, ?

Each term in the series consists of three consecutive letters in reverse order. The first letter of each term and the last letter of the next term are the same.

.
The first two terms of a sequence are 1 and 2. Each of the following terms in the sequence is the sum of all the terms which come before it in the sequence. Which of these is not a term in the sequence?

The third term of the sequence is 1 + 2 = 3, the fourth term is 1 + 2 + 3 = 6, the fifth term is 1 + 2 + 3 + 6 = 12, and so on. So the sequence begins 1, 2, 3, 6, 12, 24, 48, 96 The trick is spotting that from the 4th term onwards each term is just double the previous term. Therefore 72 does not appear.

.
When a number is divided by 13, the remainder is 11. When the same number is divided by 17, then remainder is 9. What is the number ?

x = 13p + 11 and x = 17q + 9

13p + 11 = 17q + 9

17q - 13p = 2

q =(2 + 13p) /17

The least value of p for which q =(2 + 13p) /17is a whole number is p = 26

x = (13 x 26 + 11)

= (338 + 11)

= 349

.
What is (999 âˆ’ 99 + 9) Ã· 9?

First work out the value of the expression in the brackets and then divide the result by 9. This gives (999 âˆ’ 99 + 9) Ã· 9 = 909 Ã· 9 = 101. Alternatively, we can first divide each number in the bracket by 9 and then evaluate the resulting expression. This gives (999 âˆ’ 99 + 9) Ã· 9 = (111 âˆ’ 11 + 1) = 101.

.